Introduction to the numerical modeling of groundwater and geothermal systems : fundamentals of mass, energy, and solute transport in poroelastic rocks - Bundschuh, Jochen; Suárez Arriaga, Mario César (Boca Raton, Florida : CRC Press, 2010)
Introduction -- The water problem-The UN vision -- Tne energy problem -- Multiphyusics modeling of isothermal groundwater and geothermal systems -- Modeling needs in the context of social and economic development -- The need to accelerate the use numerical modeling of isothermal aquifers and geothermal systems -- Rock and fluid properties -- Mechanical and thermal properties of porous rocks -- Linear thermoporoelastic rock deformation -- Mechanical and thermodynamical water properties -- Special properties of heterogeneous aquifers -- The problem of heterogeneity in aquifers -- The concept of multiple porosity in heterogeneous aquifers -- The triple porosity-permeability concept in geothermics -- Averages of parameters at different interfaces -- Averages for systems with two and three components: general models of mixtures --Some applications to field data -- Discontinuities of parameters when crossing heterogeneous interfaces -- Examples of heterogeneous non-isothermal aquifers -- Fluid flow, heat and solute transport -- Flow to wells in homogeneous isotropic aquifers -- Pumping test fundamentals -- Heat transport equations -- Flow of mass and energy in two-phase reservoirs -- Solute transport equations -- Principal numerical methods -- The finite difference method -- Introduction to the finite element method (FEM) -- The finite volume method (FVM) -- The boundary element method for elliptic problems -- Procedure of a numerical model elaboration -- Defining the objective of the numerical model -- Conceptual model -- Types of conceptual models -- Field data required for constructing the conceptual model -- Numerical formulation of the conceptual model -- Parameter estimation -- Selection of model type and code -- Calibration, validation and sensitivity analysis -- Performing numerical simulations -- How good is the model? Assessing uncertainties -- Model misuse and mistakes -- Example of model construction -- Parameter identification and inverse problems -- Ill-posedness of the inverse problem -- Linear least-squares (LLS) -- Nonlinear least-squares (NLS) -- Application examples -- Groundwater modeling application examples -- Periodical extraction of groundwater -- Water exchange between an aquifer and a surface water body by leakage -- Scenario modeling of multi-layer aquifers and distribution of groundwater ages caused by exploitation -- Point source contamination and aquifer remediation -- Boron contamination propagation -- Annual temperature oscillations in a shallow stratified aquifer -- Geothermal systems modeling examples -- What is geothermal energy? -- Transient radial-vertical heat conduction in wells -- The model of avdonin -- The invasion of geothermal brine in oil reservoirs -- Modeling submarine geothermal systems -- Modeling submarine geothermal systems -- Modeling processes in fractured geothermal systems.
"A Balkema book."
Incluye referencias bibliográficas e índice
Keywords: Aguas subterráneas -- Modelos matemáticos; Rocas -- Permeabilidad -- Modelos matemáticos; Materiales porosos -- Permeabilidad -- Modelos matemáticos; Teoría del transporte (física nuclear) -- Modelos matemáticos